China's journey to space from dream to reality - Xu, Jing (Created China, 2014)
The exploration of outer space has long been the subject of relentless pursuit by mankind, a pursuit which has not stopped since mankind started its journey to space in 1961. Chinese people have also never given on their dream of space exploration or stopped imagining and exploring space. This book presents the development history and the current standing of China's aerospace cause using both illustrations and pictures and in a manner of combining both the general overview and a detailed description of key events and figures within the industry. It will show you the difficult path of development that China's aerospace industry has had to take, the adversities it has faced along the way, the huge, complicated and sophisticated programs it has developed and the incredibly great prospects that it has for the future.